(untitled) (INNOVATIVE ECONOMY, 2024)
Shmyhel O.Ye. LOCAL FINANCES OF UKRAINE IN THE CONDITIONS OF MARTIAL LAW: CHALLENGES AND WAYS OF OVERCOME CRISIS PHENOMENA Purpose. The aim of the article is the study of the content of the functioning of local finances, the analysis of the main challenges and crisis phenomena arising in the field of local budgets in the conditions of the martial law of Ukraine. Methodology of research. The research was conducted using a dialectical approach to studying the current state of development of the content of local finances and financing the needs of local budgets. General scientific and special methods were used, in particular: analysis, synthesis, induction, deduction and generalization – to develop the provisions of the theory and practice of the content of local finances; monographic – when studying literary sources on issues of the content of local finances; epistemological – to clarify and deepen the content of the category "local finances"; system and analytical – when processing the information received regarding the financing of the needs of local budgets; abstract and logical – for formulating the conclusions of the study. Findings. A study of the theoretical foundations of the category "local finances" was conducted. The peculiarities of their use in the context of budgetary decentralization of territorial communities were identified. An analysis of the financing needs of local budgets under martial law was conducted. An assessment of the dynamics of revenues and expenditures of local budgets of Ukraine was carried out. The main problems of local budgets were identified. Originality. A review of literary sources was carried out to clarify the meaning of the concept of "local finances", which made it possible to offer a new understanding for optimizing the budgetary decentralization of territorial communities. Prospects for the development of financing of local budgets of Ukraine in the conditions of martial law are offered. Practical value. The obtained results of the study will contribute to increasing the effectiveness of the formation and development of financing of local budgets of Ukraine in the conditions of martial law. Key words: local finances, budget decentralization, territorial communities, local budgets, budget revenues and expenditures.